An analysis of health levels and various indicators of urban environments for Healthy Cities projects - Takano, T (BMJ Group, 2001)
STUDY OBJECTIVES—(1) To identify and to categorise the various city indicators that are related to health levels; (2) to demonstrate the extent of the influence on health of these categorised health determinants; and (3) to demonstrate both the interactive associations among the health determinants and the magnitude of influence of each health determinant on the people's health. DESIGN—By using city statistics of study areas, the health index and health determinant indices were formulated. The extent of influence of health determinants on the health index was examined by regression analysis; the interrelations between the health determinants and the health index were examined by correlation analysis. SETTING—All the administrative units in Japan with populations more than 100 000 were selected as study areas to analyse the relation of health and health determinants. MAIN RESULTS—The nine health determinant indices used—healthcare resources, preventive health activities, environmental quality, housing, urban clutter, local economy, employment, income, and education—explained 51.6% of the variances of the health index as a whole in the cities studies. The health determinant indices showed interrelations with each other, in addition to individual health determinant indices having a high correlation with the health level index of the population. CONCLUSIONS—Both individually and collectively the health determinants are closely related to the health status of a population and individual determinants interact with each other. Simultaneous analysis of the interrelations among health determinants and health status would contribute to widen integration oriented perspective in policy interventions based on collaboration between different sectors of society.   Keywords: indicators; health determinants; Healthy Cities